Proposal of serovars 17 and 18 of Actinobacillus pleuropneumoniae based on serological and genotypic analysis - Bossé, Janine T; Li, Yanwen; Sárközi, Rita; Fodor, László; Lacouture, Sonia; Gottschalk, Marcelo; Casas Amoribieta, Maria; Angen, Øystein; Nedbalcova, Katerina; Holden, Matthew T G; Maskell, Duncan J; Tucker, Alexander W; et al. (Veterinary microbiology, 2018)
The aim of this study was to investigate isolates of Actinobacillus pleuropneumoniae previously designated serologically either as non-typable (NT) or as 'K2:07', which did not produce serovar-specific amplicons in PCR assays. We used whole genome sequencing to identify the capsule (CPS) loci of six previously designated biovar 1 NT and two biovar 1 'K2:O7' isolates of A. pleuropneumoniae from Denmark, as well as a recent biovar 2 NT isolate from Canada. All of the NT isolates have the same six-gene type I CPS locus, sharing common cpsABC genes with serovars 2, 3, 6, 7, 8, 9, 11 and 13. The two 'K2:O7' isolates contain a unique three-gene type II CPS locus, having a cpsA gene similar to that of serovars 1, 4, 12, 14 and 15. The previously NT isolates share the same O-antigen genes, found between erpA and rpsU, as serovars 3, 6, 8, and 15. Whereas the 'K2:O7' isolates, have the same O-antigen genes as serovar 7, which likely contributed to their previous mis-identification. All of the NT and 'K2:O7' isolates have only the genes required for production of ApxII (apxIICA structural genes, and apxIBD export genes). Rabbit polyclonal antisera raised against representative isolates with these new CPS loci demonstrated distinct reactivity compared to the 16 known serovars. The serological and genomic results indicate that the isolates constitute new serovars 17 (previously NT) and 18 (previously 'K2:O7'). Primers designed for amplification of specific serovar 17 and 18 sequences for molecular diagnostics will facilitate epidemiological tracking of these two new serovars of A. pleuropneumoniae.
Keywords: Serotyping; Serovar 17; DNA bakterií; bakteriální pouzdra; DNA primery; PCR; Dánsko; Swine Diseases; Whole Genome Sequencing; Genotype; Serogroup; Bacterial Capsules; zvířata; Serovar 18; Capsule genes; séroskupina; Swine; sekvenování celého genomu; Canada; DNA, Bacterial; Diagnostics; Kanada; Denmark; Actinobacillus pleuropneumoniae; polymerázová řetězová reakce; nemoci prasat; DNA Primers; Polymerase Chain Reaction; genotyp; infekce bakteriemi rodu Actinobacillus; Animals; Actinobacillus Infections; prasata; sérotypizace